2017
DOI: 10.21037/jtd.2017.04.04
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic sympathectomy for hyperhidrosis: from surgical indications to clinical results

Abstract: Sympathectomy and its variations have been performed in thoracic surgery for more than 100 years. However, its indications have undergone profound modifications in this period. Likewise, since then the surgical technique has also evolved dramatically up to the minimally invasive techniques worldwide accessible in present days. Currently, primary hyperhidrosis is, by far, the main indication for thoracic sympathectomy and this procedure is usually carried out thoracoscopically with excellent results. However, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
42
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 43 publications
10
42
0
5
Order By: Relevance
“…Purtuloglu et al have reported 95% success rate in 46 patients [2]. In their big series on 407 patients with palmar hyperhidrosis, Vannucci et al reported 1% (4 cases) recurrence among their patients [14]. In our series, the recurrence was unilateral in both cases and both patients chose not to have any further intervention and we recommended trying medical management for a longer period of time.…”
Section: Discussionmentioning
confidence: 51%
“…Purtuloglu et al have reported 95% success rate in 46 patients [2]. In their big series on 407 patients with palmar hyperhidrosis, Vannucci et al reported 1% (4 cases) recurrence among their patients [14]. In our series, the recurrence was unilateral in both cases and both patients chose not to have any further intervention and we recommended trying medical management for a longer period of time.…”
Section: Discussionmentioning
confidence: 51%
“…Sympathicotomy is now the most common surgical procedure. 15 After the operation, we found that palm sweat secretion was the same or more than before the operation in some patients but disappeared 1 or 2 days later. CH may have a relationship with nerve trauma.…”
Section: Discussionmentioning
confidence: 77%
“…Better visualization of the stellate ganglion and its preservation to avoid development of post-operative Horner's syndrome. [11] As noted in many studies, the plantar domain affects considerable part of those patients of about 45% [4]; while others reported incidence of plantar domain of 70 to 100 % of patients with primary hyperhidrosis; latter researchers used extended technique of ablation from R3 to R12 to manage those cases [12]. In the Society of Thoracic Surgeons 2011 Expert Consensus for the Surgical Treatment of Hyperhidrosis [13], no recommendations for plantar domain management were noted.…”
Section: Discussionmentioning
confidence: 99%